DEVELOPMENT OF AESTHETIC EDUCATION BY TEACHING THE ART OF SCULPTURE - Abdullayeva Durdona Orifjonovna (TADQIQOTLAR.UZ, 2024)
Annotation: In this article, in the new historical period that began in Uzbekistan, creative changes in the art of sculpture, formation of a healthy spiritual environment in the country, restoration of national traditions, awareness of our historical cultural minority, and the role of sculpture in aesthetic education are covered.